2009
DOI: 10.1007/s11552-009-9245-0
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Tube Conduits in Peripheral Nerve Repair: A Retrospective Analysis

Abstract: A chart review was conducted of all patients receiving NeuraGen® conduits from 2002 to 2007 at Regions Hospital, a level I trauma center. Ninety-six patients underwent 126 repairs using NeuraGen® conduits, and 64 patients were seen in follow-up. Repairs were largely of upper extremity sensory nerves but six were repairs of nerves elsewhere in the body. There were no intra-operative complications, but there were two minor postoperative complications and one postoperative pulmonary embolus. Forty of 126 repairs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(99 citation statements)
references
References 13 publications
3
94
0
2
Order By: Relevance
“…Bushnell and colleagues [108] performed in 2008 a retrospective study of the utilization of collagen conduits in digital sensory nerve gaps of up to 20 mm and demonstrated a significant recovery rate of 89%. In a retrospective review, Wangensteen and Kalliaine [109] reported on a large number of sensory nerve gaps of 2.5-20 mm repaired with collagen conduits in multiple body regions and concluded that clinically successful outcomes were only observed in 43% of the cases. A prospective cohort study was performed by Lohmeyer and colleagues in 2009 [110] in digital and palmar nerve gaps of 6-18 mm, and results showed meaningful recovery in 75% of patients.…”
Section: Collagenmentioning
confidence: 99%
“…Bushnell and colleagues [108] performed in 2008 a retrospective study of the utilization of collagen conduits in digital sensory nerve gaps of up to 20 mm and demonstrated a significant recovery rate of 89%. In a retrospective review, Wangensteen and Kalliaine [109] reported on a large number of sensory nerve gaps of 2.5-20 mm repaired with collagen conduits in multiple body regions and concluded that clinically successful outcomes were only observed in 43% of the cases. A prospective cohort study was performed by Lohmeyer and colleagues in 2009 [110] in digital and palmar nerve gaps of 6-18 mm, and results showed meaningful recovery in 75% of patients.…”
Section: Collagenmentioning
confidence: 99%
“…The commonly used degradable materials include collagen, 46,47 chitin, 48,49 polyglycolic acid (PGA), polylactic acid (PLA), glycolide, trimethylene carbonate, 50 etc. Rosen et al compared autologous nerve graft and PGA conduit to bridge 5 mm defects in rat femoral nerve.…”
Section: Degradable Nerve Conduitsmentioning
confidence: 99%
“…The rat CSF contains numerous neurotrophic factors (nerve growth factor, fibroblast growth factor 2, ciliary neurotrophic factor) enhance peripheral nerve regeneration and neuroprotection (32). These factors may enhance the migration of Schwann cells into the guide channel, as well as proliferation, growth cone attachment on the guide channel wall and so regenerating axon elongation (17).…”
Section: Sciatic Functional Index (Sfi)mentioning
confidence: 99%
“…Collagen molecules can easily trap neurotrophic factors and collagen channels are able to adsorb cell adhesion molecules (17). Another advantage of using the collagen as a NGCs is that the degradation speed of this biological material can be controlled by manipulating the thickness of the guide channel (32).…”
Section: Sciatic Functional Index (Sfi)mentioning
confidence: 99%